2020
DOI: 10.1186/s12864-020-07096-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of miRNA and mRNA expression profiles in testes of Duroc and Meishan boars

Abstract: Background MicroRNAs (miRNAs) are small non-coding RNAs playing vital roles in regulating posttranscriptional gene expression. Elucidating the expression regulation of miRNAs underlying pig testis development will contribute to a better understanding of boar fertility and spermatogenesis. Results In this study, miRNA expression profile was investigated in testes of Duroc and Meishan boars at 20, 75, and 270 days of age by high-throug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Spermatogenesis can be divided into three major functional stages including the proliferative stage, meiosis, and maturation stage ( Griswold, 2016 ). Notably, spermatogenesis is strictly regulated by the expression of stage-specific genes at both transcription and post-transcription levels ( Ding et al, 2020 ). Thus, the testes at different developmental stages in XN cattle were taken as the experimental object in the present study, taking into consideration that identifying key regulators and signaling pathways related to testis development and spermatogenesis will provide valuable insights into improving semen quality.…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogenesis can be divided into three major functional stages including the proliferative stage, meiosis, and maturation stage ( Griswold, 2016 ). Notably, spermatogenesis is strictly regulated by the expression of stage-specific genes at both transcription and post-transcription levels ( Ding et al, 2020 ). Thus, the testes at different developmental stages in XN cattle were taken as the experimental object in the present study, taking into consideration that identifying key regulators and signaling pathways related to testis development and spermatogenesis will provide valuable insights into improving semen quality.…”
Section: Introductionmentioning
confidence: 99%
“…Sequencing technology has widely been used in animals to mine potential regulatory molecules. The ncRNAs in testis, which have been identified and functionally verified, suggest that they are involved in testicular development and sperm regulation ( 17 19 , 33 ). In this study, we constructed a linear RNA library and miRNA library.…”
Section: Discussionmentioning
confidence: 99%
“…Although a large number of lncRNAs and miRNAs have been identified and demonstrated to be involved in mammalian testicular function regulation (17)(18)(19), there are few studies on the expression of ncRNAs in different cells of the testis, especially on their regulatory mechanisms. It is valuable to study which non-coding genes maintain the normal physiological function of the testis by targeting LCs and SCs.…”
Section: Introductionmentioning
confidence: 99%
“…Among these miRNAs, a number of studies have already demonstrated their potential involvement in tissue development and immunological function. For example, a study showed that mir-423-5p may be an important regulatory molecule for testis development and fertilization [ 56 ]. miR-185 was found to promote proliferation of intestinal epithelial cells [ 57 ].…”
Section: Discussionmentioning
confidence: 99%